Lower-Limb Flexibility Profile in 142 Competitive Female Football Players: A Cross-Sectional Study - Antonio Cejudo; Riccardo Izzo; Francisco Javier Robles-Palazón; María Teresa Martínez-Romero; Pilar Sainz de Baranda (Applied Sciences)
Background/Objectives: The ROM-SPORT is a test battery for assessing flexibility that measures the range of motion (ROM) in the sport. Restricted or optimal ROM is associated with an increased risk of injury or improved athletic performance, respectively. The aim of the present study was to determine the normative values of the lower limb’s flexibility profile by ROM assessment in female football players. Methods: Lower-limb flexibility (11 ROM tests) was measured using the ROM-SPORT battery in 142 female football players (19.42 ± 4.45 years). The tests were performed at the beginning of the training sessions in the first two weeks of the pre-season. Standardized Z-scores (on a scale of 0 to 100 [T-score]) were calculated from the mean and standard deviation to classify the ROM of each movement into three qualitative categories (poor [>−3 to −2], average or normal [−1 to 1; 68.2%], and optimal [1 to >3]) and a traffic light system to facilitate interpretation of the results. Results: The results show normal (or average) ROM values at 32–37° for ankle dorsiflexion with the knee extended; 37–43° for ankle dorsiflexion with the knee flexed; 46–54° for hip internal rotation; 54–61° for hip external rotation; 31–37° for hip adduction; 70–76° for hip abduction with the hip flexed; 41–45° for hip abduction with the hip neutral; 135–141° for hip flexion; 73–82° for hip flexion with the knee extended; 15–21° for hip extension; 121–132° for knee flexion. The normative data presented in this study can be utilized by researchers and practitioners in the women’s football league in a variety of ways, provided similar data collection methods are used. Conclusions: Flexibility training is recommended to overcome normal or average ROM and optimize athletic performance with lower injury risk in female football players.